Novel Trispecific Neutralizing Antibodies With Enhanced Potency and Breadth Against Pan‐Sarbecoviruses - Rui Qiao; Yuanchen Liu; Qiyu Mao; Jiayan Li; Yinying Lu; Jialu Shi; Chen Li; Jizhen Yu; Jiami Gong; Xun Wang; Yuchen Shao; Lei Sun; et al. (MedComm)
ABSTRACT The ongoing emergence of new variants of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) underscores the urgent need for developing antivirals targeting both SARS‐CoV‐2 variants and related sarbecoviruses. To this end, we designed novel trispecific antibodies, Tri‐1 and Tri‐2, engineered by fusing the single‐chain variable fragments (scFvs) of a potent antibody (PW5‐570) to the Fc region of “Knob‐into‐Hole” bispecific antibodies (bsAbs) composed of two distinct broad antibodies (PW5‐5 and PW5‐535). Compared with the parental antibodies, Tri‐1 and Tri‐2 displayed enhanced binding affinities to the receptor‐binding domains of SARS‐CoV, SARS‐CoV‐2 wild type, and Omicron XBB.1.16, with each arm contributed to the overall enhancement. Furthermore, pseudovirus neutralization assays revealed that Tri‐1 and Tri‐2 effectively neutralized all tested SARS‐CoV, SARS‐CoV‐2 variants, and related sarbecoviruses (Pangolin‐GD, RaTG13, WIV1, and SHC014), demonstrating potency and breadth superior to any single parental antibody. Consistently, Tri‐1 and Tri‐2 were found to effectively neutralize authentic SARS‐CoV and SARS‐CoV‐2 variants with IC50 values comparable to or better than those of parental antibodies. Taken together, this study highlights the potential effectiveness of Tri‐1 and Tri‐2 as novel formats for harnessing cross‐neutralizing antibodies in the development of multivalent agents to combat both current and future SARS‐like coronaviruses.